Wanggo Gallaga's Remnants as Contribution to Philippine HIV-AIDS Literature. (2nd March 2016) - Toledo, John Leihmar Centeno
There is no poetry collection so far in the Philippines which voices the life of a person living with HIV (PLHIV). Filipino spoken word poet Wanggo Gallaga's new poetry collection, Remnants, breaks new ground for Philippine poetry written in English. Wanggo's defiance with the conventions of HIV-AIDS poetry (as compared to the distraught poems of Rafael Campo, Thomas Dunn, and Mark Doty who used the material realities and experiences of AIDS patients as their subjects) proves that there is always a rainbow after the rain. Commonly, stereotypes of brokenness, hopelessness, and wastedness are attributed to PLHIV. Wanggo subverts the norm and creates a fresh autobiographical poem, which at one point is a memoir and in another, a forgetting.